THE USE OF BLACK BAMBOO AS A SUBSTITUTE FOR COARSE AGGREGATE TO INCREASE CONCRETE COMPRESSIVE STRENGTH - Dohar Sinabutar; Yonas Prima Arga Rumbyarso (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2025)
The use of waste as an alternative building material is an effective solution to environmental problems and is popular in developing countries. On the other hand, the concrete industry, a key component of construction, continues to innovate to improve quality and efficiency. The increasing demand for concrete has driven the development of mix designs that meet strict quality and compressive strength standards, while also considering environmental sustainability. Advancements in concrete technology are driving research initiatives to improve the quality and efficiency of its use, with innovations in material selection and implementation methodologies. This aims to meet increasing demands and address construction challenges. Modern concrete is required to perform optimally in shorter timeframes, necessitating effective additives for performance enhancement. Recent research has integrated bamboo waste from the craft industry as a concrete mixture component, accelerating project implementation and providing a sustainable solution for waste management. The author is interested in conducting an in-depth study on increasing the compressive strength of concrete by integrating bamboo waste. The concrete studied has a quality of f´c 25 MPa (K-300) and was tested at 7, 14, and 28 days to assess the effectiveness of bamboo as an additive. The test results are expected to provide significant data on the viability of bamboo waste as a partial substitute for coarse aggregate. The study title, “The Use of Bamboo Waste as a Partial Substitute for Coarse Aggregate to Enhance Concrete Compressive Strength,” reflects the research objectives and the utilization of sustainable materials in modern construction. Based on the results of the research conducted and the discussion in the previous chapter with variations of black bamboo waste at 0%, 10%, and 15%, the following conclusions can be drawn: the compressive strength test results for normal concrete at 28 days reached 452 kN (fʹc 26.1 MPa = 104%), while variation 1 with 10% black bamboo waste showed a decrease in compressive strength, reaching 305 kN (fʹc 17.60 MPa = 70%), and variation 2 with 15% black bamboo waste also showed a decrease, reaching 309 kN (fʹc 17.83 MPa = 71%).